The Influence of Leadership Style, Competence and Organizational Culture on Employee Performance at PT. Buran Nusa Respati Samarinda - Nadina Anjelia Rolisa; Akhmadi (University of Widya Gama Mahakam Samarinda, 2023)
Nadina Anjelia Rolisa, The Influence of Leadership Style, Competence and Organizational Culture on Employee Performance at PT. Buran Nusa Respati Samarinda, With Supervisor I Mr. Suyanto, SE., M. Si and Supervisor II, Mr. Akhmadi, SE., MM The purpose of this study was to determine the effect and relationship of leadership style, competence and organizational culture on employee performance PT. Buran Nusa Respati Samarinda. This research method uses statistical analysis tools with the help of the SPSS ver 10 computer program to determine the effect and relationship of each variable. From the results of the analysis, it is known that the values of leadership style, competence and organizational culture as well as the performance of each employee fluctuate according to the company's activities. The results of statistical tests stated that leadership style, competency, and organizational culture jointly affect employee performance by 45%. Thus the hypothesis proposed can be accepted.